Supporting vulnerable children in the early years practical guidance and strategies for working with children at risk - Beckley, Pat (London Jessica Kingsley Publishers, 2019)
"Exploring specific experiences, circumstances and events that can put children at risk, this book provides practical guidance for early years practitioners working with vulnerable children. It covers supporting children who are abused and neglected, those with special educational needs, children from ethnic minorities, those with emotional or health difficulties, children affected by poverty and children in care. Each chapter draws on current research and theories to set out clear advice and strategies for supporting the wellbeing and development of vulnerable children, including working in partnership with parents, carers and communities"--Provided by publisher.
Part 1. The Contemporary Environment / Yinka Olusoga -- Closing the Gap: Adastra Style / Antony Luby -- Inside an Early Years Rural Setting / Nishi Bremner -- Part 2. Vulnerable Groups -- Children at Risk of Being Missed / Julia Lindley-Baker -- Language and Poverty / Elizabeth Farrar -- Children in a Diverse Society / Pat Beckley -- Looked After Children or Those in Care / Pat Beckley -- Part 3. Supporting the Child -- Safeguarding: A Journey of Transformation / Rosey Shelbourne -- Early Years Interventions / Gina Taylor -- The Quest to Determine a Child's Understanding through the Written Feedback Process / Sarah Howe, Helen Thornalley -- Exploring Approaches to Learning Outdoors / Beverley Keen -- A Positive Process / Pat Beckley -- Interminable Transition / Dr. Margaret C. Simms -- Child, Family and Community: Working with Empowering Discourses / Julie Percival, Anne Renwick, Emmy Sealey.
Includes bibliographical references and index.
Keywords: Problem youth -- Education (Primary); Children with social disabilities -- Education (Primary); Problem youth -- Behavior modification